TEACHER’S PHYSICAL PRESENCE IN THE CLASS - Qochqorova Zulfizar Abduxamid qizi; Qurbonazarova Madina Baxtiyor qizi (TADQIQOTLAR.UZ, 2023)
Abstract: This article provides information about teacher's physical presence, it is known that teacher's physical presence is one of the important issues in language teaching process .